Enhancing students' physical fitness through physical and health education teaching (1997)
This paper critically examines the ways by which students' physical fitness can be enhanced through the teaching of physical and health Education. A student of physical and health Education should be physically fit if the objectives of the subject were to be met. The paper emphasizes that there is need to develop both the health related physical fitness components and performance-related physical fitness components of students through chalkboard classroom teaching practical teaching of various games and sports and during training for school sports. The benefit of physical fitness is not limited to an individual but it is also an index to any Country's National posture. The vigour of any Country is no stronger than the vitality and will of her Country men.